Evaluation of tissue blood supply during esophagectomy using fluorescent diagnostics and diffuse scattering spectroscopy in visible region - Anna A. Krivetskaya; Daniil M. Kustov; Vladimir V. Levkin; Sergey V. Osminin; Sergey S. Kharnas; Evgenia V. Eventeva; Fedor P. Vetshev; Roman N. Komarov; Kirill G. Linkov; Tatiana A. Savelieva; Victor B. Loschenov (Photodiagnosis and Photodynamic Therapy)
Background: The success of the surgical treatment of a tumor or obstruction of the esophagus with subsequent anastomosis application depends on the level of blood supply to the stitched tissues. Intraoperative assessment of blood flow is widely used in medicine and can be used as a diagnostic method that affects the outcome of surgery and reduces the frequency of postoperative complications for the patient. Methods: In this work, the assessment of blood supply during esophageal resection operations was carried out using two techniques sequentially: fluorescent diagnostics with indocyanine green and measurement of hemoglobin oxygen saturation by diffuse scattering spectroscopy in the visible wavelength range. The first method was used to assess the integrity of the vascular network structure in the area of anastomosis and blood flow through the sutured tissues, the second one – for local assessment of hemoglobin oxygen saturation in the investigated area. Results: Conducted clinical study involved the participation of nine patients with malignant neoplasms (six cases) or esophageal obstruction (three cases). The presence of postoperative complications was compared with the measurement results. Anastomosis failure was observed in only one patient. According to the results of the study, with the use of the investigated method of assessing blood supply, there is a tendency towards a decrease in the frequency of anastomosis leaks (11.1 % compared with 21.4 %). Conclusions: Therefore, fluorescent diagnostics with indocyanine green and measurement of hemoglobin oxygen saturation using diffuse scattering spectroscopy were affirmed as methods that allow increasing the safety of surgical procedures by assessing the risk of postoperative complications, including anastomosis failures.